The Relationship between Moral Sensitivity and Professional Behaviour and Its Comparison in First- and Last-Year Undergraduate Nursing Students - Maryam Bagheri; Mohsen Shahriari; Pegah Hassanvand; Akram Mohammadi Pelarti; Afarin Ghanavatpour (Nursing Research and Practice)
Background. Nursing students should be equipped with ethical sensitivity and professional behaviour because they will face challenging ethical issues in their future work environment. This study aimed to determine the relationship between moral sensitivity and professional behaviour and compare it in first- and last-year undergraduate nursing students. Methods. This study was a cross-sectional, correlational study that was conducted at Isfahan University of Medical Sciences in 2019. The sample size of this study was 238 nursing students. The tools used in this study were the Persian versions of the moral sensitivity questionnaire and the professional behaviour questionnaire. The data were analyzed using SPSS 18 software. Results. Linear regression showed that the total score of moral sensitivity of nursing students had a significant relationship with their professional behaviour p < 0.05. The result of the univariate analysis showed that the mean total score of moral sensitivity and professional behaviour was significantly higher in the last year than in first-year students p < 0.05. Conclusion. Considering the relationship between moral sensitivity and the professional behaviour of nursing students, the promotion of moral sensitivity can become the basis for the development of the professional behaviour of nursing students. Therefore, it is suggested to focus on teaching the principles of nursing ethics to develop the moral sensitivity of undergraduate nursing students.